Transient receptor potential cation channel, subfamily C, member 5 (TRPC5) is a cold-transducer in the peripheral nervous system - Zimmermann, Katharina; Lennerz, Jochen K.; Hein, Alexander; Link, Andrea; Kaczmarek, J. Stefan; Delling, Markus; Uysal, Serdar; Pfeifer, John D.; Riccio, Antonio; Clapham, David E. (Proceedings of the National Academy of Sciences of the United States of America, 2011)
Detection and adaptation to cold temperature is crucial to survival. Cold sensing in the innocuous range of cold (>10-15 °C) in the mammalian peripheral nervous system is thought to rely primarily on transient receptor potential (TRP) ion channels, most notably the menthol receptor, TRPM8. Here we report that TRP cation channel, subfamily C member 5 (TRPC5), but not TRPC1/TRPC5 heteromeric channels, are highly cold sensitive in the temperature range 37-25 °C. We found that TRPC5 is present in mouse and human sensory neurons of dorsal root ganglia, a substantial number of peripheral nerves including intraepithelial endings, and in the dorsal lamina of the spinal cord that receives sensory input from the skin, consistent with a potential TRPC5 function as an innocuous cold transducer in nociceptive and thermosensory nerve endings. Although deletion of TRPC5 in 129S1/SvImJ mice resulted in no temperature-sensitive behavioral changes, TRPM8 and/or other menthol-sensitive channels appear to underpin a much larger component of noxious cold sensing after TRPC5 deletion and a shift in mechanosensitive C-fiber subtypes. These findings demonstrate that highly cold-sensitive TRPC5 channels are a molecular component for detection and regional adaptation to cold temperatures in the peripheral nervous system that is distinct from noxious cold sensing.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Nociception; Pain; Single-fiber; Temperature sensing; Thermo-transient receptor potential